Solution of one boundary-value problem for a hyperbolic equation of the second order - Khoma, S. G. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We find conditions for the existence of the classical solution of the boundary-value problem u tt -u xx = f(x,t), u(0,t)=u(π, t)=0, u(x, 0)=u(x, 2π).